Investigation of coeliac trunk and superior mesenteric artery variations and literature review. - Hadi Sasani; Nergiz Ekmen (National Scientific Medical Center, 2021)
Aim:To evaluate the variations of coeliac trunk and superior mesenteric artery variations in Tekirdag province using computed tomography (CT) images. Methods: The data of the patients who underwent CT angiography for any reason via the hospital online PACS system were scanned retrospectively for celiac trunk and superior mesenteric artery variation. The frequency of variation in the study population, the variation type and distribution by gender were statistically analyzed. Results: A total of 2529 individuals, including 1703 (67.3%) men and 826 (32.7%) women, were included in the study. The prevalence of variation in the study group was 25.7% (n=650), and it was seen that there was a single variation in 579 (89.1%) individuals and a double variation in 71 (10.9%) individuals. The three most common variations were replaced right HA, LGA orginated replaced left HA, and common HA from SMA origin ( n= 340, 13.44 % ; n=120, 4,74 % and n=46, 1.82 %,  respectively). Conclusion: Information the rates of these vascular variations provides contribution to surgical procedures and prevents more serious complications. Also, it should be carefully investigated in terms of other accompanying variation.